Becoming Language Teachers: Exploring Student-teachers’ Identities Construction through Narratives - Torres-Cepeda, Nancy María; Ramos-Holguín, Bertha (GIST – Education and Learning Research Journal, 2019)
This paper reports on the findings of a qualitative narrative study. Its aim was to analyze what student-teachers’ narratives unveiled about the construction of their identity as language learners, and the connections made with being future in-service teachers. This study, which was carried out with undergraduate students from a public university in Tunja, was the product of permanent interaction and dialogue with student-teachers in their initial teaching experiences. Narratives, in-depth interviews, and journals were used as data collection instruments. Data were analyzed using the grounded theory approach. The results suggest that student-teachers construct and re-construct their identities as language learners and future teachers across classroom interactions and their empowerment through teaching and reflection